2010
DOI: 10.3892/ijo_00000749
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of induced MYCN hyper-expression in MYCN-amplified neuroblastomas

Abstract: Abstract. Neuroblastoma is a childhood malignancy of the sympathetic nervous system. The tumor exhibits two different phenotypes: favorable and unfavorable. MYCN amplification is associated with rapid tumor progression and the worst neuroblastoma disease outcome. We have previously reported that inhibitors of histone deacetylase (HDAC) and proteasome enhance favorable neuroblastoma gene expression in neuroblastoma cell lines and inhibit growth of these cells. In this study, we investigated the effect of Tricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Our previous study indicated that elevated p53 expression has a suppressive effect on MYCN expression in MYCN -amplified neuroblastoma cells ( 8 ). We thus investigated whether this was also the case in the S(+)-ibuprofen-treated cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study indicated that elevated p53 expression has a suppressive effect on MYCN expression in MYCN -amplified neuroblastoma cells ( 8 ). We thus investigated whether this was also the case in the S(+)-ibuprofen-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed as previously described ( 8 , 9 ). Light emission signals were captured by a LAS-3000 (Fujifilm) digital image analyzer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome inhibitor alters cellular protein homeostasis and has shown to prevent MYCN degradation resulting in its accumulation with a deleterious effect in MYCN-driven neuroblastomas [55,56]. Bortezomib was also selected based on single-agent activity and promising features in combination studies in pediatric preclinical models [20,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Protein stability is controlled by a number of signalling pathways including mTOR, 37 whereas mRNA stability may be dependent on a variety of miRNAs and proteins including HuD and members of the p53 family. 35 , 38 , 39 , 40 However, developmentally, MYCN expression will be controlled by suppression of transcription and this is likely to be the principal mechanism by which MYCN is downregulated in the Kelly cells, although a contribution by factors regulating mRNA and protein stability cannot be ruled out. The key factors that initiate suppression of MYCN expression remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%